A multi-perspective cost-effectiveness analysis comparing rivaroxaban with enoxaparin sodium for thromboprophylaxis after total hip and knee replacement in the German healthcare setting - Zindel Sonja; Stock Stephanie; Müller Dirk; Stollenwerk Björn (BMC, 2012)
Abstract Background Patients undergoing major orthopaedic surgery (MOS), such as total hip (THR) or total knee replacement (TKR), are at high risk of developing venous thromboembolism (VTE). For thromboembolism prophylaxis, the oral anticoagulant rivaroxaban has recently been included in the German diagnosis related group (DRG) system. However, the cost-effectiveness of rivaroxaban is still unclear from both the German statutory health insurance (SHI) and the German hospital perspective. Objectives To assess the cost-effectiveness of rivaroxaban from the German statutory health insurance (SHI) perspective and to analyse financial incentives from the German hospital perspective. Methods Based on data from the RECORD trials and German cost data, a decision tree was built. The model was run for two settings (THR and TKR) and two perspectives (SHI and hospital) per setting. Results Prophylaxis with rivaroxaban reduces VTE events (0.02 events per person treated after TKR; 0.007 after THR) compared with enoxaparin. From the SHI perspective, prophylaxis with rivaroxaban after TKR is cost saving (€27.3 saving per patient treated). However, the cost-effectiveness after THR (€17.8 cost per person) remains unclear because of stochastic uncertainty. From the hospital perspective, for given DRGs, the hospital profit will decrease through the use of rivaroxaban by €20.6 (TKR) and €31.8 (THR) per case respectively. Conclusions Based on our findings, including rivaroxaban for reimbursement in the German DRG system seems reasonable. Yet, adequate incentives for German hospitals to use rivaroxaban are still lacking.